Coral transplantation: An introducing and practicing to fisheries community group organization at Sidoasri, Malang - Oktiyas Muzaky Luthfi; Daduk Setyohadi; Dhira Khurniawan Saputra; Akhmad Zainuri (Future Science, 2018)
Decreasing fisheries product at Sidoasri, Malang has been caused by many factors and the main caused this problem is damage of coral reef ecosystem in that area. Coral reef damage may be caused by anthropogenic and natural factors, but if massive or longterm damage of coral reef will affected on decreasing income of local fishermen that dependent on reef product. Coral transplantation is one of method to restore coral into natural as before damage. Transplantation using coral fragment will increase coral recovery due to using asexual to regenerate coral into new colonies. Basic knowledge of transplantation should be transferred into fishermen so they can duplicate and practices by their self. Correct way of coral transplantation is key successful of this rehabilitation program in the future.